2013
DOI: 10.1371/journal.pntd.0002344
|View full text |Cite
|
Sign up to set email alerts
|

Mini-FLOTAC, an Innovative Direct Diagnostic Technique for Intestinal Parasitic Infections: Experience from the Field

Abstract: BackgroundSoil-transmitted helminths and intestinal protozoa infection are widespread in developing countries, yet an accurate diagnosis is rarely performed. The aim of this study was to evaluate the recently developed mini–FLOTAC method and to compare with currently more widely used techniques for the diagnosis of intestinal parasitic infections in different settings.Methodology/Principal FindingsThe study was carried out in Dharamsala, Himachal Pradesh, India, and in Bukumbi, Tanzania. A total of 180 pupils … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
105
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(122 citation statements)
references
References 19 publications
10
105
0
7
Order By: Relevance
“…However, mini-FLOTAC-ZnSO 4 was the most accurate for diagnosis of helminthic infection, and FEC was more accurate in the diagnosis of protozoal infection (accuracy = 100%, CI = 1.0-1.0, and perfect agreement with the gold standard, κ index = 1), a result that corresponds to that of Barda and others. 41 Quantitative diagnosis of H. nana infections showed that the Kato-Katz technique significantly detected more eggs than mini-FLOTAC techniques (P < 0.001). However, no significant difference was found in quantitative diagnosis of E. vermicularis egg count (P = 4).…”
Section: Discussionmentioning
confidence: 97%
“…However, mini-FLOTAC-ZnSO 4 was the most accurate for diagnosis of helminthic infection, and FEC was more accurate in the diagnosis of protozoal infection (accuracy = 100%, CI = 1.0-1.0, and perfect agreement with the gold standard, κ index = 1), a result that corresponds to that of Barda and others. 41 Quantitative diagnosis of H. nana infections showed that the Kato-Katz technique significantly detected more eggs than mini-FLOTAC techniques (P < 0.001). However, no significant difference was found in quantitative diagnosis of E. vermicularis egg count (P = 4).…”
Section: Discussionmentioning
confidence: 97%
“…However, our study has shown that integration is feasible in the Sri Lankan context. Improved tests like mini-FLOTAC that can test preserved stools 26 and involvement of additional university parasitology laboratories might be necessary if this program were to be expanded to cover the entire country. Unpublished draft WHO guidelines for integrating STH screening with TAS call for~300 children to be tested for STH per EU, because this is sufficient for classifying areas for further treatment after cessation of MDA for filariasis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that Mini-FLOTAC is more sensitive than the formol-ether concentration method and direct smear for the diagnosis of soil-transmitted helminths in humans, than the McMaster technique for the diagnosis of Eimeria in goats (Barda et al, 2013a(Barda et al, , 2013b(Barda et al, , 2013cSilva et al, 2013).…”
Section: Discussionmentioning
confidence: 99%